Influence of Timing and Predicted Risk on Mortality in Impella-Treated Infarct-Related Cardiogenic Shock Patients - Schäfer, Andreas; Werner, Nikos; Burkhoff, Daniel; Sieweke, Jan-Thorben; Zietzer, Andreas; Masyuk, Maryna; Junker Udesen, Nanna Louise; Westenfeld, Ralf; Møller, Jacob Eifer (Frontiers in Cardiovascular Medicine, 2020)
Background: In-hospital mortality in acute myocardial infarction-related cardiogenic shock (AMI-CS) remains high. The only adequately powered randomized trial showed no benefit of routine us of the intra-aortic balloon pump in AMI-CS. We compared individually predicted mortality using CardShock- and IABP-Shock II-scores in AMI-CS patients treated with an Impella microaxial pump, who met the IABP-Shock II-trials inclusion/exclusion criteria, to observed mortality on circulatory support in order to determine whether standardised use of an Impella microaxial flow-pump in AMI-CS is associated with lower than predicted mortality rates and whether timing of implantation or selecting patients based on predicted risk is meaningful. Methods and Results: We analyzed data from 166 consecutive Impella-treated AMI-CS patients meeting the inclusion/exclusion criteria of the IABP-Shock II-trial (age 64±11 years). 39% (n=64) had been resuscitated before Impella implantation. Overall 30-day mortality was 42%. Mortality was higher in resuscitated patients (50% vs. 36%, p=0.0452) and when Impella was implanted post-PCI (Impella-pre-PCI: 28%, Impella-post-PCI: 51%, p=0.0039). While in both score systems there was no significant difference between predicted and observed overall 30-day mortality, predicted mortality was significantly higher than observed mortality on Impella support only for individuals with highest predicted risk based on CardShock score (predicted 77% vs observed 51%, p=0.025). Conclusions: Our retrospective analysis suggests that the use of the Impella microaxial pump may be effective in selected cases of high risk patients with AMI-CS.